Team Work In Hospital And The Role Of Medical Social Specialist - Al Enazi, Noura Zahir (Journal of Humanities & Social Sciences, 2019)
According to the previous analysis we can summarize the results of the current study as the following: 1-Study showed the availability of all good team work properties in Hospital with middle degree. 2- it’s showed that the availability of good team work properties in Hospital are ordered ascending according to the responses of work team members as the following: -The intact relationships among the difference. -The periodical revision for team works. -The suitable leadership of team. -The intact method in work. -The individual growth of work team members. -The clarified objectives for team. -Co-operation between Work team members. -Exchange of confidence and support among work team members. -Frankness and facing among work team members. 3- it’s showed that there is not existing statistic differences in responses of study sample members around the extent of availability for all good team work properties in Hospital is referred to functional name variable for workers. 4- it has been reached to the existence of statistic differences in responses of study sample members around the extent of availability for all good team work properties in Hospital is referred to experience years in work, and differences in the interest of who of a short experience in work. 5- it’s showed that there is not existing statistic differences in responses of study sample members around the extent of availability for all good team work properties in Hospital is referred to scientific specification variable for social specialists. 6-it’s showed that there is not existing statistic differences in responses of study sample members around the extent of availability for all good team work properties in Hospital is referred to training courses variable in work for medical field. 7- it’s showed that there is not existing statistic differences in responses of study sample members around the extent of availability for all good team work properties in Hospital is referred to training courses variable in team work field. The study seek to recognize on the extent of availability for good team work properties in medical Institution. Study Objectives: Generally, This study aims to recognizing the extent of availability for good team work properties in medical Institution, Through Knowledge: - Extension of clarity of objectives among work team members in the medical institution.- Extension of availability of frankness and facing among team work members in the medical institution. - Extension of exchanging confidence and support among team work members in the medical institution. - Extension of co-operation among team work members in the medical institution. - Recognizing on the extension of using intact method in work in the medical institution. - Recognizing on extension of suitability of leadership for team in medical institution. - Recognizing on the extension of availability the periodical revision for team works in the medical institution. - Recognizing on the extension of team interest with individual growth for it’s members in the medical institution. - Recognizing on the extension of availability for intact relationships among the different teams in the medical institution. The methodological procedures: Can be identified in the following main steps: Study kind: Annalistic descriptive study. Study methodology: Social Survey method. Environment and study sample: Study Environment consists of all workers in the medical king Abdulaziz city in Riyadh, that by the exclusive counting for social specialists and style of class sample technique for the rest of workers from doctors, nurses, administrators and nutritionist specialists. Data collecting tool: The researcher depended on a questionnaire for workers in King Abdulaziz Medical City in Riyadh, and the questionnaire included two main parts, taking care of including enough information for replying the queries of this study.